PERSONAL PERSON TAXPAYER COMPLIANCE TESTING HAS AN EFFECT AS AN INTERVENING VARIABLE BETWEEN THE IMPACT OF THE IMPLEMENTATION OF THE E-FILING SYSTEM ON TAX REVENUES IN KPP PRATAMA MEDAN BELAWAN - Ritonga, Pandapotan; Anggreani, Tuti (Accounting and Business Journal, 2021)
Private person taxpayers who report SPT, with a very low number of e-filings are not comparable to the taxpayers of registered private persons. This is due to a lack of knowledge, understanding of e-filing, and taxpayer indifference in the use of e-filing, due to busyness factors. So the interest or interest of taxpayers in reporting annual SPT through e-filing is very low. The purpose of the research to find out the taxpayer compliance testing of private people has the effect of intervening between the impact of the E-Filing System on tax receipts at KPP Pratama Medan Belawan. This study uses an associative approach. The population in this study was a private taxpayer e-filing user registered with KPP Pratama Medan Belawan with a sample of 100 respondents. Data collection techniques are used with questionnaires and documentation studies. The results of this study prove that the implementation of the E-Filing System has an impact on Taxpayer Compliance, Taxpayer Compliance impacts tax receipts, and the implementation of the e-filing system impacts tax receipts through Taxpayer Compliance at KPP Pratama Medan Belawan. All private taxpayers in Indonesia who already work or have income are required to report annual SPT online. In addition to being more effective and practical and saving time.